PREDIÇÃO DO CICLO DE CORTE DE ESPÉCIES ARBÓREAS COMERCIAIS POR GRUPOS ECOLÓGICOS EM UMA FLORESTA NA AMAZÔNIA BRASILEIRA - OLIVEIRA, Larissa Corrêa Lopes Quadros; JARDIM, Fernando Cristovam da Silva; GOMES, Jaqueline Macedo (Brazilian Journal of Biometrics, 2020)
This research aimed to prognosis the diameter distribution of the forest using the Transition Matrix model for species classified as tolerant, intolerant and intermediate and to define the cutting cycle by ecological groups, in order to verify if the time defined in the Brazilian environmental legislation is compatible with the recovery and growth of tree species. The research area is located in Moju, Pará, Brazil. Nine clearings were selected, around which 4 sample plots of 500 m² were installed. All individuals with DBH ≥ 5 cm were measured. For the prognosis, actual data of the years 2007 and 2010 were used and the projections were made for a 3 years period. With predicted data, the volume estimation was performed up to 31 years after the lumbering. It was found that for the tolerant and intolerant species, the ideal cutting cycle is 16 years, and for the intermediate ones, 22 years.